Two new fungal genera (Diaporthales) found on Dipterocarpaceae in Thailand - Tang, Xia; Lu, Yong-Zhong; Dissanayake, Lakmali S.; Goonasekara, Ishani D.; Jayawardena, Ruvishika S.; Xiao, Yuan-Pin; Hyde, Kevin D.; Chen, Xue-Mei; Kang, Ji-Chuan (Frontiers in Microbiology, 2023)
Diaporthales is a species-rich order of fungi that includes endophytes, saprobes, and pathogens associated with forest plants and crops. They may also occur as parasites or secondary invaders of plant tissues injured or infected by other organisms or inhabit living animal and human tissues, as well as soil. Meanwhile, some severe pathogens wipe out large-scale cultivations of profitable crops, timber monocultures, and forests. In this study, we introduce two new genera of Diaporthales found on Dipterocarpaceae in Thailand, namely Pulvinaticonidioma and Subellipsoidispora, based on morphology and phylogenetic analyses of combined ITS, LSU, tef1-α, and rpb2 sequence data. Pulvinaticonidioma is characterized by solitary, subglobose, pycnidial, unilocular conidiomata with the internal layers convex and pulvinate at the base; hyaline, unbranched, septate conidiophores; hyaline, phialidic, cylindrical to ampulliform, determinate conidiogenous cells and hyaline, cylindrical, straight, unicellular, aseptate conidia with obtuse ends. Subellipsoidispora has clavate to broadly fusoid, short pedicellate asci with an indistinct, J- apical ring; biturbinate to sub-ellipsoidal, hyaline to pale brown, smooth, guttulate ascospores that are 1-septate and slightly constricted at the septa. The phylogenetic analyses based on ITS, LSU, tef1-α, and rpb2 combined sequence data, generated from maximum likelihood (ML), maximum parsimony (MP), and MrBayes (BI) suggested that Pulvinaticonidioma and Subellipsoidispora are novel genera related to Cryphonectriaceae and Coryneaceae, respectively.